The comparative anthropology of religion, or the anthropology of religion compared: a critical comment - Hausner, SL (Wiley, 2020)
In this commentary, I argue that we need to expose the multiple layers of historical thinking about the production of the category of religion that play into both our scholarly thinking and the way religion is lived, understood and fought for in the lives of our informants. We can no more take the contours (or limits) of any particular religion for granted, or as self‐evident, than we can take the category of religion, named as such, as a natural human phenomenon that is somehow free from the domain of culture.